Concert album for orchestra - PRENDIVILLE, Harry (ed) (Leo Feist)
Ave MarianAngel's SerenadenAnvil Chorus from Il-TrovatorenApple BloosomsnAmaryllisnCavalieria RusticananFifth Hungarian dancenFlower songnLa MorsarianLa PalomanLion Du BalnLove's dream after the BallnPizzacato PolkanSchubert's SerenadenSimple aveunSpring song